Cervical Pessary for Preventing Preterm Birth in Singleton Pregnancies With Short Cervical Length: A Systematic Review and Meta-analysis. Issue 1 (January 2018) - Saccone, Gabriele; Ciardulli, Andrea; Xodo, Serena; Dugoff, Lorraine; Ludmir, Jack; Pagani, Giorgio; Visentin, Silvia; Gizzo, Salvatore; Volpe, Nicola; Maruotti, Giuseppe Maria; Rizzo, Giuseppe; Martinelli, Pasquale; et al.
Abstract : (Abstracted from J Ultrasound Med 2017;36:1535–1543) Spontaneous preterm birth (SPTB) is the leading cause of perinatal death in the United States and other countries. A short cervical length (CL) is a predictor of SPTB, and cervical pessaries have been found in some studies to decrease the rate of preterm birth.